La necesidad de fomentar el vínculo geografía-salud - León Brito, Alder Luis (Mediciego, 2020)
The versatility of the geographic sciences has allowed them to forge their scientific work beyond the fields of knowledge and interest that characterized them at the beginning, as they ventured into related sciences as well as in the branches of the economy (production, trade and services).